Fishers’ Job Satisfaction in the Caribbean - Iris Monnereau; Victor Ruiz; Richard Pollnac (Études Caribéennes)
A variety of researchers have carried out job satisfaction studies in fisheries during the last decades. Results have shown the significant role of self-actualization in the determination of job satisfaction which backs the reasoning that fishing is more than just a livelihood. This paper is based in a job satisfaction study carried out in three lobster fisheries in the Caribbean. Lobster fishing (Panulirus argus) is an important economic activity throughout the Caribbean Basin, both as a source of income and employment for the local population as well as foreign exchange for national governments. These countries differ significantly in structure of the fishery as well as governance arrangements. In this paper we wish to address the relation between these structural differences and fishers’ job satisfaction across the three countries. Results indicate fishers’ job satisfaction is significantly higher in small-scale fisheries.